The Role of the Economic TV Programs (Shows) in Promoting Financial Inclusion - Kadhim Al-Essa, Mohammed R. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACTThe present research seeks to reinforce the role of economic TV. shows in promotion for the financial inclusion concept within the Iraqi Central Bank strategy of the years (2016-2020). It aims at finding out different levels of exposure to economic TV. shows, and their patterns. It also aims to obtain information of the data, which these shows introduce to reinforce the concept of financial inclusion and their contribution in reducing poverty rates and creating security and economic stability.